2020
DOI: 10.1016/j.cell.2020.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Proteogenomic Characterization across Major Histological Types of Pediatric Brain Cancer

Abstract: Highlights d Proteogenomics characterization of 218 pediatric brain tumor samples of 7 histologies d Proteomic clusters reveal actionable biological features spanning histological boundaries d Proteomics reveal downstream effects of DNA alterations not evident in transcriptomics d Kinase activity analyses provide insights into pathway activities and druggable targets

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
195
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(202 citation statements)
references
References 211 publications
7
195
0
Order By: Relevance
“…It has been shown that the plasma level of metabolites of interest can help to define the grading of brain glioma and to provide prognostic information in patients with a similar glioma grade [ 87 ]. Nevertheless, data are still rare for these emerging approaches; however, the promise of precision medicine and the surge of multimodal data-driven strategies can provide valuable tools for the development of biomarkers and innovative therapies in glioblastomas [ 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the plasma level of metabolites of interest can help to define the grading of brain glioma and to provide prognostic information in patients with a similar glioma grade [ 87 ]. Nevertheless, data are still rare for these emerging approaches; however, the promise of precision medicine and the surge of multimodal data-driven strategies can provide valuable tools for the development of biomarkers and innovative therapies in glioblastomas [ 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…The loss of correlation between RNA and protein highlights the need for protein evidence-based investigations, for example pediatric cancer subtypes were identified based on only proteome data (Petralia et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Proteomics and metabolomics are areas with opportunities for expanded understanding of gliomas. Nevertheless, inter-and intra-tumor differences in proteome profile have been reported in small series of adult patients [102][103][104], and in pediatric neuro-oncology [105]. Multi-institutional studies in adult populations are needed, aiming to identify molecular targets not observed from RNAseq data, as gene expression data often does not correlate highly to changes in proteomic expression.…”
Section: Future Directionsmentioning
confidence: 99%